A fully Lagrangian formulation for fluid-structure interaction problems with free-surface flows and fracturing solids. (1st July 2021) - Cornejo, Alejandro; Franci, Alessandro; Zárate, Francisco; Oñate, Eugenio
Highlights: Fluid structure interaction. Free surface flows and fracturing solids. Natural disaster simulation. Abstract: This paper presents a novel coupled formulation for fluid-structure interaction (FSI) problems involving free-surface fluid flows, fracture phenomena, solid mutual contact and large displacements. The numerical formulation combines three different Lagrangian computational methods. The Particle Finite Element Method (PFEM) is used to solve the free-surface fluid flow, a Finite Element Method (FEM) with smoothed isotropic damage model is employed for the solution of solid structures and debris, finally, the Discrete Element Method (DEM) is used to manage the contact interaction between different solid boundaries, including the new ones generated by propagating cracks. The proposed method has a high potential for the prediction of the structural damages on civil constructions caused by natural hazards, such as floods, tsunami waves or landslides. Its application field can also be extended to fracture phenomena in structures and soils/rocks arising from explosions or hydraulic fracking processes. Several numerical examples are presented to show the validity and accuracy of the numerical technique proposed.